Attack on nigerian college : Boko Haram’s War on western education? - Ahmed Salah Hashim (2014)
The attack on students of an agricultural college in northeastern Nigeria by the militant Boko Haram underscores the group's violent strategy against western education. Security measures by authorities have proved ineffective to curb the violence against state institutions.